Effect of Vitamin D on Experimental Autoimmune Neuroinflammation Is Dependent on Haplotypes Comprising Naturally Occurring Allelic Variants of CIITA (Mhc2ta) - Sonja Hochmeister; Shahin Aeinehband; Charles Dorris; Rasmus Berglund; Michaela T. Haindl; Vid Velikic; Vid Velikic; Sven A. Gustafsson; Tomas Olsson; Fredrik Piehl; Maja Jagodic; Manuel Zeitelhofer; et al. (Frontiers in Neurology, 2020)
An increasing body of evidence associates low vitamin D levels with increased risk of multiple sclerosis (MS), suggesting the possibility of a gene-environment interaction for this environmental factor in MS pathogenesis. Moreover, it has been shown that vitamin D downregulates major histocompatibility complex (MHC) class II expression in experimental autoimmune encephalomyelitis (EAE), an animal model of MS. We here report about the impact of a dietary vitamin D supplementation on EAE in the rat strains having functionally relevant allelic variations in the CIITA (Mhc2ta) gene, a master regulator of MHC class II expression. Full length myelin oligodendrocyte glycoprotein (MOG)-EAE was induced in DA.PVGav1-Vra4 congenic rats harboring the Vra4 locus from PVG strain in the EAE- susceptible DA background, and compared to the parental strains. The congenic rats fed with either vitamin D supplemented, deprived or regular diet developed an intermediate clinical EAE phenotype, in contrast to DA and PVG strains. Immunopathological studies revealed vitamin D dose-dependent effect on demyelination and inflammatory infiltration of the central nervous system (CNS), expression of MHC class II and CIITA, as well as downregulation of a range of pro-inflammatory genes. Taken together, our findings demonstrate an impact of vitamin D on the target tissue pathology and peripheral immune response during EAE in DA.PVGav1-Vra4 congenic strain. Thereby, our data provide evidence of a modulatory effect of vitamin D in context of genetic variances in the Vra4 locus/Mhc2ta gene in MS-like neuroinflammation, with potential relevance for the human demyelinating disease.